SISTEM INFORMASI ADMINISTRASI PERUSAHAAN PADA PT. ANUGRAH BERKAH GRUB BERBASIS WEBSITE: Project-Based Learning, Human-Computer Interaction, UI/UX, learning outcomes, student creativity. - Mulyati , Sri; Afrizal; Jodi Setiawan (JURNAL AKADEMIKA, 2025)
PT. Anugrah Berkah Grup is a car rental service company located in Jambi City. Since its establishment in 2022, the company has encountered administrative challenges, such as managing customer records, rental transactions, and financial reports, which are still conducted manually and lack integration with digital systems. This has led to inefficiencies and ineffectiveness in data management and business processes, potentially hindering the company’s growth. This research aims to design and develop a web-based car rental information system to help PT. Anugrah Berkah Grup manage customer data, transactions, and financial reports in a more structured and effective manner. The research utilizes the Waterfall methodology, covering stages of requirements analysis, design, implementation, and maintenance. The result of this research is a web-based car rental information system that facilitates data management, improves efficiency, and enhances customer service. With this system, PT. Anugrah Berkah Grup is expected to optimize its operations and support its business growth in the future.